Hard-Candy Consumption Does Not Have an Effect on Volume and pH of Gastric Content in Patients Undergoing Elective Gastrointestinal Endoscopic Procedures: A Randomized Controlled Trial [Corrigendum] - Somnuke P; Kitisin N; Chumklud P; Kunavuttitagool P; Deepinta P; Wadrod A; Prachayakul W; Amornyotin S; Raykateeraroj N (Dove Medical Press, 2024)
Somnuke P, Kitisin N, Chumklud P, et al. Ther Clin Risk Manag. 2022;18:1049–1057. The authors have advised that there is an error in the Materials and Methods, Study Design section. Page 1050, first paragraph, line three, the text “(approval number SI188/2564)” should read “(approval number Si 342/2021)”. The authors apologize for this error.